The groundlessness usage of the English borrowings of different semantic types in the publicistic texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The functioning of some English borrowings which have negative influence on the lexical system of the Ukrainian language is determined in the article. It is also proved that the authors of the publicistic texts while selecting the English borrowings are followed by linguistic fashion and they ignore some orthographic norms of the Ukrainian language.
Keywords: English borrowings; publicistic style; negative influence; orthographic norms